(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
People in the past relied more on the environment for their survival. Because of how reliant theywere on plants for survival, they learned to use the economic and therapeutic potential of several plantspecies. The Rig Veda, considered by many to be the oldest storehouse of human knowledge, has thefirst references to the usage of plants for therapeutic purposes in Hindu culture. India has an extensivehistorical background in the use of plant-based medicines for medicinal and preventative purposes. In thestudy review the antimicrobial acitivity of some medicinal plant.